IMPLEMENTASI NILAI SUFISTIK DI ERA DIGITAL TERHADAP KEISTIQOMAHAN SANTRI ASRAMA ASSHOFIYAH PONDOK PESANTREN DARUL ULUM - Arya Dzamar Ar Rofi’, Muhammad; Rahman Hakim, Syarif; Yazid, Syaifulloh Yazid (IAIN Madura, 2025)
This study aims to explore how Pondok Pesantren Darul Ulum Peterongan Jombang implements sufistic values in the digital era and identifies the challenges and opportunities faced by the pesantren in maintaining istiqomah amidst modernity. This research utilizes a descriptive qualitative method with data collected through observations, in-depth interviews, and documentation. The findings indicate that Pondok Pesantren Darul Ulum Jombang successfully integrates sufistic values into the curriculum and daily activities of the students through various approaches such as routine dzikir, the study of classic Islamic texts (kitab kuning), the habituation of sunnah practices, and the exemplary behavior of the caretakers and teachers. Spiritual activities such as istighosah, mujahadah, and khotmil Qur’an strengthen the students' commitment to worship and enhance their spiritual awareness. The moral and adab education provided also significantly contributes to shaping the students' character to be polite, humble, and respectful towards others. The main supporting factors in forming the students' humility include the support from the surrounding community and competent human resources. Overall, the implementation of sufistic values at Pondok Pesantren Darul Ulum Peterongan Jombang demonstrates the effectiveness of spiritual approaches in strengthening character education and developing individuals who are ready to contribute positively to society.